The effects of different casting parameters on the microstructure and mechanical properties of titanium dental implant - Soydemir, Necati. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Dental implants are used to replace the missing teeth instead of dental bridges. Titanium (Ti) and its alloys are suitable to be the material for dental implants due to their excellent mechanical properties, good corrosion resistance in biological fluids and biocompatibility. But, Ti is a difficult metal to cast because of its high melting point (1670 ± 50 ºC) and great reactivity at high temperatures with elements such as oxygen, hydrogen and nitrogen. By using centrifugal casting, this problem is minimized. Also, in this method, larger force acting on the molten metal is a big advantage to produce sound castings. The objective of this study is to find the differences between the structures and mechanical properties of dental implants that were produced with different casting parameters (raise time and revolution per minute, rpm). Specimens later are annealed at 700°C to check the microstructure change and Vickers microhardness (HV) values. Ti Grade 4 (unalloyed pure Ti) was used in this study. ZPrinter 310 equipment (Z Corporation, USA) was used for modelling (rapid prototyping). Wax models were produced by using mould silicone. For casting, a high frequency melting & casting unit (Vacutherm 3.3 Titan, Linn High Therm GmbH, Germany) was used. It has been found that raising centrifugal speed made a slight decrease in HV. 300/1 Annealed (AN) specimen has the highest HV value. Annealing made a slight increase in HV. After annealing, microstructure is changed and most of the acicular α grains are converted to α grains.
Keywords: Titanium.; Dental implants.